An improved wide ZVS soft‐switching range PWM bidirectional forward converter for low power applications with simple control circuit. Issue 15 (4th June 2022) - Bahrami, Hamid; Allahyari, Hesamodin; Adib, Ehsan
Abstract: This paper presents a new PWM (Pulse Width Modulation) ZVS (Zero Voltage Switching) bidirectional forward DC‐DC converter. The proposed bidirectional forward converter uses two main switches and employs the leakage inductance of the transformer to transfer the power. Two auxiliary capacitors are paralleled with the main switches to provide the ZVS soft‐switching condition and to reset the transformer core. Having two main switches, one transformer, and two auxiliary capacitors makes the proposed converter simple and low cost. Compared with the main counterpart, the proposed converter uses PWM which is really simple relative to the phase shift voltage matching control approach. Moreover, to provide the ZVS soft switching conditions, the magnetizing inductance value should be large which decreases the circulating current and increases the efficiency significantly in both boost and buck directions especially at the low power. The ZVS soft‐switching conditions can be maintained from low power to full load. The operating modes of the proposed converter along with the design approach and the stress analysis are completely considered. To verify the theoretical results, a prototype is constructed and the theoretical results are compared with the experimental results.